1999
DOI: 10.1109/23.819155
|View full text |Cite
|
Sign up to set email alerts
|

Proton damage effects on p-channel CCDs

Abstract: An experimental batch of p-buried channel CCDs has been fabricated and characterised for proton-induced radiation damage. Dark current effects were similar to conventional nchannel CCDs, but radiation-induced changes in charge transfer inefficiency were reduced by approximately a factor 3 for -30°C operation and background signal -2,000 electrons/pixel; though this is a lower limit and further reduction may be possible in future CCD batches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 14 publications
5
36
0
Order By: Relevance
“…Evolution of dark durrent in proton irradiated CCD (device 4) compared to 60 Co irradiated CCD (device 9) constants are poorly constrained, the values agree quite well with the values from the two term fit to the proton-irradiated data.…”
Section: Results Of 60 Co Irradiationsupporting
confidence: 67%
See 1 more Smart Citation
“…Evolution of dark durrent in proton irradiated CCD (device 4) compared to 60 Co irradiated CCD (device 9) constants are poorly constrained, the values agree quite well with the values from the two term fit to the proton-irradiated data.…”
Section: Results Of 60 Co Irradiationsupporting
confidence: 67%
“…The LBNL p-channel CCDs are fabricated on high-resistivity n-type silicon with boron implanted channels. In the p-channel CCDs, divacancy states are expected to be the dominant hole trap [7]- [9]. It has been predicted that divacancy formation in p-channel CCDs is less favorable than phosphorus-vacancy traps in n-channel CCDs [8], and prior studies have shown improved performance after radiation exposure [7], [10], [11].…”
Section: Ccd Requirementsmentioning
confidence: 99%
“…As pointed out by Spratt et al [5] and Hopkinson [6], the dominant hole trap expected after proton irradiation of a p-channel CCD is the divacancy. Divacancy formation is considered to be less favorable in a p-channel CCD compared to P-V formation in an n-channel CCD.…”
Section: Radiation Damagementioning
confidence: 99%
“…Proton displacement damage effects on CCDs have also been extensively investigated. [6][7][8][9][10] Histograms of dark current in p-buried channel CCDs irradiated by 10 MeV protons are available in the literature. 6 Dark signal spikes in EEV three phase CCDs irradiated by 40 MeV protons are investigated.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] Histograms of dark current in p-buried channel CCDs irradiated by 10 MeV protons are available in the literature. 6 Dark signal spikes in EEV three phase CCDs irradiated by 40 MeV protons are investigated. 7 Mean degradation of dark current and DSNU induced by proton irradiation from 17 to 100 MeV are analyzed.…”
Section: Introductionmentioning
confidence: 99%